Pengaruh Penambahan Molases Terhadap Komposisi Kimia Silase Beberapa Jenis Rumput Yang Ditanam Bercampur Dengan Stylos - M. Yunus (Agricultural Faculty, 2007)
ABSTRACT. This study was conducted in UPTD (Unit Pelaksana Tugas Dinas) Saree Aceh Besar about 4 weeks. The matter of this study are 4 kinds of grass there are rumput benggala (panicum maximum) rumput BD (Brachiaria decumbent). The grass that use in this study ditanam mixe with stylosanthes guyanesis legume, while the additive in silage is molasses. The study was designed into Completely Randomized Design (CDR) Factorial 4x3. There were 3 replications. First factor was R1 (Rumput Benggala + Stylosanthes guyanesis), R2 (Rumput lampung+Stylosanthes guyanesis), R3 (Rumput BD + Stylosanthes guyanesis), R4 (Rumput Star grass +Stylosanthes guyanesis) and the second factor were 3 level there were M1 (0%0,M2(3%) dan M3 (5%). Invetigated variabes included pH, Dry matter, crude protein, crude fiber, ash and water containet..The data were analyzed by an analysis of variance and as a significant effect was detected, the analysis was contained by Uji Beda Nyata Terkecil (BNT), Steel and Torrie (1991). The result of this study showed that the different of several grass have hight significantly (P,0.010 of dry matter, crude protein, ash and water containing but have no significantly on pH and crude fiber silage. The diferent among molasses have significantly on pH, crude protein and crude fiber silage. From BNT test showed that molasses increased dry matter and crude protein of silage compared to no molasses added. However, th used of molasses decreased crude fiber and water contain compared to no molasses added. The quality of silage found at level of 5.5% molasses especially on star grass (R4M3). The study concluded that using different level molasses es on several grass producted better silage than without molasses.